Pengaruh Kepemimpinan Kepala Desa Terhadap Kinerja Pegawai Di Kantor Desa Cikande Kecamatan Saguling Kabupaten Bandung Barat - Yunita Fourina Dewi; Susilawati (Relasi : Jurnal Ekonomi, 2025)
This study aims to examine the influence of village head leadership on employee performance at the Cikande Village Office, Saguling District, West Bandung Regency. The method used is a descriptive method with a quantitative approach, while the data collection technique is carried out by distributing questionnaires to a number of respondents, literature studies, observations, and interviews. From the results of the respondents' responses to the variable (X) obtained 76% while the variable (Y) obtained a score of 77%, then from the results of the hypothesis test t_hitung 23,573 and t_tabel 2,086, then t_hitung> t_tabel so that Ho was rejected and Ha was accepted, which means that Leadership has a significant effect on Employee Performance. Based on the correlation coefficient between the X variable (Leadership), and the Y variable (Employee Performance) of 0.994, it is proven that there is a positive and significant relationship between the X variable (Leadership) and the Y variable (Employee Performance).Meanwhile, based on the coefficient of determination (KD), it is known that the achievement of the ability of variable X has an effect on variable Y, which is 98.80% while the remaining 1.20% is influenced by other variables that are not studied in this study. Based on the results of the research, it can be stated that the leadership variables and employee performance variables are good. Some of the suggestions that the researcher conveyed need to hold training or socialize to employees about improving a good attitude in serving the community who come, providing socialization to employees to comply with their obligations in attending work, working deftly quickly and accurately and minimizing mistakes in their work and increasing the number of employees, so that at the time of service many people do not have to wait for time that is too long.